Efektivitas Manajemen Strategi Kelembagaan Islam dalam Peningkatan Kualitas Pelayanan Pendidikan - Ramadana, Alief Aulia; Muslim, M. Paris; Irfan, Nadir; Hafiz, Abdul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
. This research investigates strategic approaches in Islamic institutional management with a focus on integrating digital technology and adapting strategies across various regions in Indonesia. Through Systematic Literature Review (SLR) method, we explore existing literature to identify methods, challenges, and best practices applied in Islamic institutions. The findings indicate that while strategies like SWOT analysis and Balanced Scorecard are widely used to enhance operational effectiveness, there is still a need to further integrate digital technology in strategic management to broaden service reach and improve efficiency. This research is expected to provide valuable guidance for the development of adaptive and effective Islamic institutional management in the current era of digitalization and globalization.